2017
DOI: 10.1007/s12035-016-0372-7
|View full text |Cite
|
Sign up to set email alerts
|

Carnosic Acid Suppresses the H2O2-Induced Mitochondria-Related Bioenergetics Disturbances and Redox Impairment in SH-SY5Y Cells: Role for Nrf2

Abstract: The phenolic diterpene carnosic acid (CA, CHO) exerts antioxidant, anti-inflammatory, anti-apoptotic, and anti-cancer effects in mammalian cells. CA activates the nuclear factor erythroid 2-related factor 2 (Nrf2), among other signaling pathways, and restores cell viability in several in vitro and in vivo experimental models. We have previously reported that CA affords mitochondrial protection against various chemical challenges. However, it was not clear yet whether CA would prevent chemically induced impairm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 102 publications
4
11
0
Order By: Relevance
“…4A). The main mechanism may involve regulation of ERK, Keap1/Nrf2, PI3K/Akt, and the c-fos signaling pathway [37][38][39][40].…”
Section: Discussionmentioning
confidence: 99%
“…4A). The main mechanism may involve regulation of ERK, Keap1/Nrf2, PI3K/Akt, and the c-fos signaling pathway [37][38][39][40].…”
Section: Discussionmentioning
confidence: 99%
“…Yang et al verified that HO-1, upregulated by pterostilbene, suppressed mitochondrial oxidative stress in vitro and in vivo in an experimental model of cerebral ischemia reperfusion injury [40]. Marcos et al demonstrated that inhibition of HO-1 or silencing of Nrf-2 blocked the protective effects of Carnosic acid on mitochondria-related redox parameters and function, which explicated a role of the Nrf-2/HO-1 axis in the maintenance of mitochondrial function during oxidative stress [41]. Our present study showed that MaR 1 increased nuclear Nrf-2 and cytosolic HO-1 expression in lung tissue after ischemic reperfusion.…”
Section: Discussionmentioning
confidence: 99%
“…Naringenin, one of the flavonoids identified in HEG, has been described as modulating the activity of the enzymes superoxide dismutase, glutathione peroxidase, and catalase, in addition to protecting the cell membrane against the lipid peroxidation process by inhibiting the production of malondialdehyde and increasing the content of thiol-SH groups [ 43 ]. In turn, diterpenes promote the scavenging of free radicals, which results in the inhibition of lipid peroxidation [ 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%